“Tem que ser do nosso jeito, não do jeito deles!”: a educação escolar indígena entre os Xukuru-Kariri (AL) - Oliveira, Italo Dennis de (2019)
This dissertation aims to analyze the process of construction and development of school education among the Xukuru-Kariri in the Aldeia Fazenda Canto, in Palmeira dos Índios (AL). For this purpose, the political, social and cultural changes that took place in the context, especially those driven by the “territorialization process”, were taken into consideration, with attention to the cultural reworking carried out at school guided by the current emphasis on ethnicity. It was considered necessary to explain the emergence and standardization of discourses about indigenous school education, highlighting the importance of the performance of the indigenous movement since the 1970s, which brings reverberations to the present day. Approach the dynamics of conformation of alliances between different agents and agencies in the context in focus, the negotiations and disputes between the social actors in this “political arena”, trying to highlight the variations of positions among the social actors. The analysis focused on understanding how the Xukuru-Kariri build and design the school institution based on their experiences and expectations, built through interaction and dialogue with different agents and agencies. In this sense, some strategies developed by the Xukuru-Kariri stand out in response to the State impositions that arise with the indigenous school education project, especially after the 1988 Constitution. It was also necessary to address the collective action of the young Xukuru-Kariri, which converges with the agenda of the indigenous movement and presents itself as a process of reworking the relationship with different agencies and the state. The work, based on a procedural approach, seeks to contribute to studies on indigenous school education, highlighting the role of indigenous people in the face of state impositions and the multifaceted character of the school institution in a specific context.